2020
DOI: 10.1021/acsomega.9b03423
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on Surface Treatments of Biodegradable Mg Alloys: A Review

Abstract: Mg alloys have attracted extensive attention in the biomedical fields owing to their great biocompatibility, suitable mechanical properties, and biodegradability, etc. However, the fast degradation rate restricts the application of Mg alloys. Thus, the surface treatment of Mg alloys is considered as one of the most effective ways to enhance the corrosion resistance of Mg alloys. Nevertheless, simple processing to improve the corrosion resistance can no longer meet the growing biofunctional clinical requirement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 50 publications
(74 reference statements)
0
16
0
Order By: Relevance
“…Therefore, it is necessary to control the degradation rate of magnesium alloys for realizing long-term implantation. At present, surface modifications are considered to be an effective way to improve the corrosion resistance of magnesium alloys [ 9 , 10 , 11 , 12 , 13 , 14 ]. Among all of the various surface modifications, the MAO coatings have been widely employed on Mg alloys due to its metallurgical adhesion to the substrate, good wear resistance, moderate corrosion resistance, and high hardness [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to control the degradation rate of magnesium alloys for realizing long-term implantation. At present, surface modifications are considered to be an effective way to improve the corrosion resistance of magnesium alloys [ 9 , 10 , 11 , 12 , 13 , 14 ]. Among all of the various surface modifications, the MAO coatings have been widely employed on Mg alloys due to its metallurgical adhesion to the substrate, good wear resistance, moderate corrosion resistance, and high hardness [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…High corrosion rate of magnesium-based alloys in tissue environment may be limited, in addition to modifying the chemical composition, by surface treatment technologies. The degradation process can be controlled by way of coating the surface or changing its structure [53,60,61]. There are two methods of coating: conversion and deposition processes.…”
Section: Methods Of Reducing the Degradation Rate Of Magnesium Alloysmentioning
confidence: 99%
“…• Micro-arc oxidation (MAO) -is considered the most cost-effective technology in the production of protective coatings against corrosion on Mg-based alloys. Surface pores and cracks, which accelerate the corrosion rate, are a significant disadvantage of this technology [60,63].…”
Section: Methods Of Reducing the Degradation Rate Of Magnesium Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnesium alloy has emerged as a potential biomaterial owing to its biodegradability, good mechanical strength, and biocompatibility. [1][2][3] The Young's modulus of Mg alloys is similar to that of bone, avoiding stress shielding effect, which occurs for other metallic implant materials with high Young's modulus. 4 Researchers reported that Mg metal may be qualified to serve as a suitable bone scaffold material to be used in tissue engineering.…”
Section: Introductionmentioning
confidence: 99%